2021
DOI: 10.3390/toxins13020137
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Neurotoxin Injections in Childhood Opisthotonus

Abstract: Opisthotonus refers to abnormal axial extension and arching of the trunk produced by excessive contractions of the paraspinal muscles. In childhood, the abnormal posture is most often related to dystonia in the setting of hypoxic injury or a number of other acquired and genetic etiologies. The condition is often painful, interferes with ambulation and quality of life, and is challenging to treat. Therapeutic options include oral benzodiazepines, oral and intrathecal baclofen, botulinum neurotoxin injections, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…Table 1 presents a summary of our findings. Four open-label studies reported outcomes after treatment for dystonia associated with CP, the so-called dyskinetic cerebral palsy (DCP) [13][14][15][16], while others focused on focal dystonia [17,18] or opisthotonos [19]. Three case reports reported outcome measures of patients with a defined genetic condition associated with generalized dystonia: pantothenate kinase-associated neurodegeneration (PKAN) [20,21] and Hallervorden-Spatz syndrome (HSS) [22].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Table 1 presents a summary of our findings. Four open-label studies reported outcomes after treatment for dystonia associated with CP, the so-called dyskinetic cerebral palsy (DCP) [13][14][15][16], while others focused on focal dystonia [17,18] or opisthotonos [19]. Three case reports reported outcome measures of patients with a defined genetic condition associated with generalized dystonia: pantothenate kinase-associated neurodegeneration (PKAN) [20,21] and Hallervorden-Spatz syndrome (HSS) [22].…”
Section: Resultsmentioning
confidence: 99%
“…Most studies reported on patients treated with Onabotulinum toxin type A (Ona BTA) (Botox) [13,16,19,21,24] or Abobotulinum toxin type A (Abo BTA) (Dysport) [17,20,22,23] or both [15], while two studies reported injection of Rimabotulinum toxin type B (Rima BTB) (Myobloc) [14,18]. The BT dose ranged from 4 to 23.8 U/kg for Ona BTA, from 4.8 to 30 U/kg for Abo BTA and from 50 to 200 U/kg for Rima BTB.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations